2022
DOI: 10.3390/diagnostics12041014
|View full text |Cite
|
Sign up to set email alerts
|

Semiautomated Segmentation and Volume Measurements of Cervical Carotid High-Signal Plaques Using 3D Turbo Spin-Echo T1-Weighted Black-Blood Vessel Wall Imaging: A Preliminary Study

Abstract: Unstable carotid plaques are visualized as high-signal plaques (HSPs) on 3D turbo spin-echo T1-weighted black-blood vessel wall imaging (3D TSE T1-BB VWI). The purpose of this study was to compare manual segmentation and semiautomated segmentation for the quantification of carotid HSPs using 3D TSE T1-BB VWI. Twenty cervical carotid plaque lesions in 19 patients with a plaque contrast ratio of > 1.3 compared to adjacent muscle were studied. Using the mean voxel value for the adjacent muscle multiplied by 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…This classification ( Table 2 ) highlights the ability of MR imaging to detect plaques based on composition and morphology. In addition, magnetization-prepared rapid acquisition with gradient-echo (MPRAGE) can display plaque bleeding with high specificity ( 24 , 25 ). Over the past 5 years, a series of studies has demonstrated that 3.0T high-resolution MR carotid plaque imaging is highly consistent with histopathological results ( 24 ).…”
Section: Imaging Identification Of Vulnerable Carotid Plaquementioning
confidence: 99%
“…This classification ( Table 2 ) highlights the ability of MR imaging to detect plaques based on composition and morphology. In addition, magnetization-prepared rapid acquisition with gradient-echo (MPRAGE) can display plaque bleeding with high specificity ( 24 , 25 ). Over the past 5 years, a series of studies has demonstrated that 3.0T high-resolution MR carotid plaque imaging is highly consistent with histopathological results ( 24 ).…”
Section: Imaging Identification Of Vulnerable Carotid Plaquementioning
confidence: 99%